(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Filipinos typically enjoy sipping on refreshing drinks like samalamig and buko juice. However, recently, a new product was developed. Milk tea has become popular in the Philippines. This business created distinctively designed drinks to encourage consumers to share pictures of their drinks on social media. The popularity of milk tea quickly went viral and attracted a lot of attention. This study was to evaluate the factors that contribute to the business’s success. The goal of this study is to ascertain how many variables affect how successful a business is. The study also looks into the possibilities that came their way and the difficulties they faced while operating their business. This study exposed that the difference was not significant between the assessment of administrator and employee group of respondents in the factors that influence the business success in terms of vision, mission, goals, and objectives; organizational structure; job descriptions and policies; and rules and regulations. This was validated by the t-computed value of 5.5, which is greater than the t-critical value of 2.712 at a 0.01 level of significance and 38 degrees of freedom. Having these compared values, the null hypothesis was rejected. The results showed the difficulties experienced by the two groups of respondents, mainly ineffective management, competitors, out-of-scope work, and dishonesty. However, the respondents undertook the following solutions: Collaborate with the employees to increase efficiency and productivity; Promote the company’s product strength; Enhance knowledge and skills; Establish employment agreements and corporate policies. The proposed development plan can be crafted to enhance the level of business success. This includes the key result area on vision, mission, goals, and objectives; organizational structure; job descriptions; and policies, rules, and regulations. Furthermore, the researchers proposed recommendations and development plans to help the administrators and employees enhance and guide the business to success.